A study of hot pixels induced by proton and neutron irradiations in charge coupled devices. Issue 5 (3rd May 2020) - Liu, Bingkai; Li, Yudong; Wen, Lin; Zhou, Dong; Feng, Jie; Ma, Lindong; Zhang, Xiang; Cai, Yulong; Wang, Zhiming; Fu, Jing; Guo, Qi; Ma, Ding
ABSTRACT: Charge coupled devices with high sensitivity and low dark current were irradiated separately by 10 MeV proton, 14 and 1 MeV neutron up to the fluences of 10 9  cm − 2 . The generation pattern of hot pixels at different conditions is presented. The experimental results demonstrate that the nuclear inelastic scattering is the dominant generation mechanism of hot pixels induced by proton and neutron irradiations. Meanwhile, a theoretical model is used to predict hot pixel tails at different annealing time points and different operating temperatures.